1997
DOI: 10.1086/304135
|View full text |Cite
|
Sign up to set email alerts
|

High‐Density, Compact HiiRegions in the Starburst Galaxies NGC 3628 and IC 694: High‐Resolution VLA Observations of the H92α Radio Recombination Line

Abstract: Using the Very Large Array (VLA), we have observed the H92a line in the nuclear regions of NGC 1 3628 and Arp 299 (IC 694 ] NGC 3690) with an angular resolution of 1A. The radio recombination lines could provide quite important constraints to the physical conditions for the ionized gas in the nuclear regions. For the central nuclear components in NGC 3628, IC 694, and NGC 3690, we Ðnd that the electron density of the ionized gas is in the range 5 ] 102 to 5 ] 104 cm~3, with corresponding geometrical sizes rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
44
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 21 publications
10
44
0
Order By: Relevance
“…Neff et al 2002, private communication) that is also associated with an NIR source (not identified by AH00). Its relatively soft X-ray colors suggest that it may be associated with a radio supernova, as was originally proposed by Huang et al (1990), rather than a background QSO (Zhao et al 1997). …”
Section: Multiwavelength Associationsmentioning
confidence: 71%
See 4 more Smart Citations
“…Neff et al 2002, private communication) that is also associated with an NIR source (not identified by AH00). Its relatively soft X-ray colors suggest that it may be associated with a radio supernova, as was originally proposed by Huang et al (1990), rather than a background QSO (Zhao et al 1997). …”
Section: Multiwavelength Associationsmentioning
confidence: 71%
“…We also find an X-ray counterpart (source 8) for a radio source in the east of CЈ, which we will refer to as CЉ ( , ; h m s a p 11 28 31.7 d p ϩ58Њ33 49Љ .5 J2000). In addition, we have detected an X-ray counterpart (source 10) of the radio source IC 694ϩ1990 (which lies 5Љ southwest of component A; Huang et al 1990;Zhao et al 1997;S. Neff et al 2002, private communication) that is also associated with an NIR source (not identified by AH00).…”
Section: Multiwavelength Associationsmentioning
confidence: 74%
See 3 more Smart Citations